2012
DOI: 10.1093/jpids/pis055
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of an Ambulatory-Based Antibiogram for Uropathogens in Children: Table 1.

Abstract: Unnecessarily broad-spectrum antibiotic prescribing for ambulatory pediatric urinary tract infection may result from clinicians not having antibiograms specific to this population. Comparing an existing hospital-based with a proposed ambulatory uropathogen antibiogram for children in Utah, Escherichia coli accounted for a larger percentage and was more susceptible to narrower-spectrum antibiotics, demonstrating the potential need for ambulatory pediatric antibiograms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 9 publications
5
23
0
Order By: Relevance
“…10,11 Dahle et al recently examined different susceptibility patterns of urinary isolates in a single health care system, comparing a community based uropathogen antibiogram to a hospital based uropathogen antibiogram for children in Utah. 5 Similar to our findings, they determined that there was a difference in resistance patterns between outpatient and inpatient uropathogens. We evaluated whether outpatient vs inpatient resistance patterns would follow similar trends on a larger, broader scale.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…10,11 Dahle et al recently examined different susceptibility patterns of urinary isolates in a single health care system, comparing a community based uropathogen antibiogram to a hospital based uropathogen antibiogram for children in Utah. 5 Similar to our findings, they determined that there was a difference in resistance patterns between outpatient and inpatient uropathogens. We evaluated whether outpatient vs inpatient resistance patterns would follow similar trends on a larger, broader scale.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings extend what was previously found in single center studies. 5,9 The different resistance patterns in outpatient and inpatient settings affect empirical antibiotic choices when treating a child with a UTI. Clinicians must choose an antibiotic with a high likelihood of coverage while considering potential adverse effects and minimizing unnecessary overuse of broadspectrum antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Moreover, most antibiograms are from hospital based laboratory data, and a recent study from Dahle et al showed that these data may provide inaccurate information about antibiotic resistance patterns for ambulatory pediatric patients. 20 Thus, the goal should be to promote separate institutional guidelines for hospital and community based patients derived from local data to optimize empirical prescribing choices and reduce the use of unnecessarily broad agents or antibiotics with known higher resistance rates.…”
Section: Discussionmentioning
confidence: 99%
“…While no additional resources are required to separate results based on patient age, hospitals often combine susceptibility data for adults and children. Dahle and colleagues demonstrated differences between inpatient and outpatient resistance patterns and recommended separate antibiograms by visit setting [Dahle et al 2012]. In a recent study (unpublished data), inpatient and outpatient urinary isolates from children under 18 years were examined using The Surveillance Network, and compared 25,418 outpatient and 5560 inpatient urinary isolates.…”
Section: Improving Antibiotic Prescribing Patternsmentioning
confidence: 99%